KELAYAKAN MATERI AJAR SASTRA DARI KOMPONEN NILAI PENDIDIKAN KARAKTER BUKU BAHASA INDONESIA SMP KELAS VII - Leli Nisfi Setiana, Meilan Arsanti, dan Oktarina Puspita Wardani, Aida Azizah, (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
Indonesian language textbooks are the main source of teaching and learning activities used by teachers and students and are used as a reference for gathering information as well as supporting learning activities. The appropriateness of the content of the material is one part of the criteria in the assessment of textbooks. The main problem in this study is how the appropriateness of the content of literary teaching materials, especially the fairy tales of the components of character education values contained in the contents of the Indonesian language book for grade VII SMP. The purpose of this research is to describe the feasibility of the content of literary teaching materials, especially fairy tales from the components of the character education values contained in the Indonesian language book for grade VII SMP.